2014
DOI: 10.17795/whb-23654
|View full text |Cite
|
Sign up to set email alerts
|

Report on the Second Iranian International Conference on Women’s Health Held May 1 and 2, 2013 in Shiraz, IR Iran

Abstract: Women’s health is increasing identified as a global health priority. Women’s health is affected by many factors, such as the economy, environment, society, culture, religion, and biology. For this reason, the Health Policy Research Center, Shiraz, Iran decided to hold The First Iranian International Conference on Women’s Health. The aim of this conference was to provide up-to-date information on different aspects of women’s health, including healthy aging, non-communicable and communicable diseases, psycho-soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…A local Iranian study to evaluate the knowledge of mothers with under-five children about diarrhea reported inadequate knowledge about the diagnosis and treatment of diarrhea among this group of mothers (25), emphasizing the need for direct educational programs towards this target population. In this regard and according to the promotion of health literacy in women, an international conference on women's health is annually held in Iran (26).…”
Section: Death Per 1000 Livebirthsmentioning
confidence: 99%
“…A local Iranian study to evaluate the knowledge of mothers with under-five children about diarrhea reported inadequate knowledge about the diagnosis and treatment of diarrhea among this group of mothers (25), emphasizing the need for direct educational programs towards this target population. In this regard and according to the promotion of health literacy in women, an international conference on women's health is annually held in Iran (26).…”
Section: Death Per 1000 Livebirthsmentioning
confidence: 99%
“…It is estimated that infertility affects between 8% and 12% of reproductive-aged couples worldwide (Afkhamzadeh et al, 2021). The overall prevalence of infertility in Iran was 7% in 2021 and the prevalence by gender was higher in women (Maharlouei et al, 2021). Furthermore, although infertility is a problem among couples, most of its social burden lies with women (Inhorn and Patrizio, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, about half of the women, 15 to 64 years of age were overweight or obese and had low physical activity and only 2% of them had no risk factor (6). Therefore, the mean age is at least 10 years younger than women with the same malignancy in developed countries and a longer period of time is spent with the disease (5).…”
mentioning
confidence: 99%
“…Therefore, the mean age is at least 10 years younger than women with the same malignancy in developed countries and a longer period of time is spent with the disease (5). Women with BC in Iran due to some cultural issues encounter many psychosocial stresses and physical problems (6), and unfortunately the role of husbands in supporting patients and fostering selfefficacy in Iranian BC patients is low (7).…”
mentioning
confidence: 99%